2012
DOI: 10.1111/j.1532-5415.2012.04238.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Longitudinal Measures of Renal Function and Onset of Dementia in a Community Cohort of Older Adults

Abstract: Background Prior studies have described a higher incidence of dementia or worsening cognitive function in patients with lower levels of kidney function at a single point in time. Objectives To evaluate the association between dynamic measures of renal function ascertained over time with onset of dementia. Design prospective community cohort study. Setting and Participants 2,968 adults aged 65 and older followed for the development of dementia over a median of 6.0 years (interquartile range 3.1–10.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
“…24 Another study of 2968 adults aged 65 years or older found that increased eGFR variability, but not eGFR trajectory, was associated with an increased risk for dementia. 25 Thus, the existing literature supports the hypothesis that changes in cognitive function parallel changes in markers of kidney function.…”
Section: Discussionmentioning
confidence: 70%
“…The Adult Changes in Thought (ACT) Study found that those with lower eGFR had a higher incidence of dementia over 6 years of follow up, however there was no significance in adjusted analyses. 32 There were trends toward higher incident dementia among those with positive eGFR trajectories and greater variability in eGFR over time. The Osaki-Tajiri Project is a community-based study including 497 subjects (45% men) over 65 in an agricultural area of northern Japan.…”
Section: Discussionmentioning
confidence: 92%